2007
DOI: 10.1080/j006v27n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of the Short Child Occupational Profile (SCOPE)

Abstract: The purpose of this study was to examine the reliability and validity of the Short Child Occupational Profile (SCOPE; version 2.0). The SCOPE is an occupation focused, client-centered, theory driven assessment developed out of a practice/academic partnership. In this study, twenty practitioners from occupational therapy, physical therapy, speech therapy, and social work completed thirty-five SCOPE assessments with clients' ages two years, four months to twenty-one years with both physical and intellectual disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…These tools promote reflection on the affective experience of participation, which may give some indication of a young person's satisfaction with their constellation of daily activities. A less structured assessment of time use and participation is offered by the Occupational Circumstances Assessment Interview and Rating Scale (Forsyth et al ., 2005), the Model of Human Occupation Screening Tool (MOHOST) (Parkinson, Forsyth & Kielhofner, 2006), and the Short Child Occupational Self Assessment (Bowyer, Ross, Schwartz, Kielhofner & Keller, 2005) (a paediatric version of MOHOST, currently under development). Information gained through these sorts of assessment tools may identify if activity participation is restricted, limiting exposure to developmental opportunities.…”
Section: Relevance To Occupational Therapy Practicementioning
confidence: 99%
“…These tools promote reflection on the affective experience of participation, which may give some indication of a young person's satisfaction with their constellation of daily activities. A less structured assessment of time use and participation is offered by the Occupational Circumstances Assessment Interview and Rating Scale (Forsyth et al ., 2005), the Model of Human Occupation Screening Tool (MOHOST) (Parkinson, Forsyth & Kielhofner, 2006), and the Short Child Occupational Self Assessment (Bowyer, Ross, Schwartz, Kielhofner & Keller, 2005) (a paediatric version of MOHOST, currently under development). Information gained through these sorts of assessment tools may identify if activity participation is restricted, limiting exposure to developmental opportunities.…”
Section: Relevance To Occupational Therapy Practicementioning
confidence: 99%
“…Rasch analysis (Rasch, 1960(Rasch, /1980 has guided the development of the SCOPE and has been used to provide evidence of the psychometric properties. A previous study of the SCOPE, conducted within one clinical setting, supported the psychometric soundness of the instrument overall, but pointed to some potential problems in practitioners' use of the SCOPE (Bowyer, Kramer, Kielhofner, Maziero-Barbosa, & Girolami, 2007). Specific revisions were made to the SCOPE to address particular practitioner rating behaviors.…”
mentioning
confidence: 92%
“…Rater effects are systematic variances in ratings that are associated with the rater and not the performance of the client (Myford & Wolfe, 2004a). Previous research on the SCOPE showed that some rater effects commonly discussed in the literature, including leniency/severity, halo, and restriction of range, may be present when practitioners rate clients using the assessment (Bowyer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While the CHIEF, CASE and ECEQ and one item of the M2PI overtly examine the environment relative to participation (e.g., aspects which hinder or facilitate participation), this link is less apparent in items in the HOME Inventory, FILE and MSPSS. Details on validity, reliability and responsiveness and clinical utility of the included measures are in Tables 2, 3 and 4 respectively. The authors are aware of one measure not identified in the initial systematic search of the literature or subsequent reference scanning/citation tracking, which is relatively new, specifically the Short Child Occupational Profile (SCOPE) (Bowyer, Kramer, Kielhofner Maziero-Barbosa, & Girolami, 2007). The SCOPE is a measure developed for use by occupational therapists, and is based on a theoretical model (the 'Model of Human Occupation' [MOHO]) that defines participation as 'engagement in work, play, or activities of daily living that are part of one's cultural context and desired for their wellbeing' (Bowyer et al, 2007, p. 69;Kielhofner, 2002).…”
Section: Resultsmentioning
confidence: 99%